Therapeutic targeting of acute myeloid leukemia stem cells - Pollyea, Daniel A; Jordan, Craig T (Blood, 2017)
For more than 50 years, investigators have considered a malignant stem cell as the potential origin of and a key therapeutic target for acute myeloid leukemia (AML) and other forms of cancer. The nature and existence of tumor-initiating cells for leukemia and other malignancies have long been the subject of intense and rigorous study; indeed, the promise of the potential to eradicate such cells is clear. However, until recently, deficiencies in our understanding of the nature of these cell populations, coupled with a limited ability to therapeutically exploit their weaknesses, have been limiting factors in realizing the goal of targeting leukemic stem cells (LSCs). Exciting new insights into the fundamental underpinnings of LSCs are now being made in an era in which drug development pipelines offer the potential to specifically target pathways of significance. Therefore, the focus in this new era, characterized by the confluence of understanding LSCs and the ability to target them, is shifting from "if it can be done" to "how it will be done." Moving from a theoretical stage to this hopeful era of possibilities, new challenges expectedly arise, and our focus now must shift to determining the best strategy by which to target LSCs, with their well-documented heterogeneity and readily evident intra- and interpatient variability. The purpose of this review is therefore both to summarize the key scientific findings pertinent to AML LSC targeting and to consider methods of clinical evaluation that will be most effective for identifying successful LSC-directed therapies.